2021
DOI: 10.1177/00315125211011728
|View full text |Cite
|
Sign up to set email alerts
|

Information Processing and Technical Knowledge Contribute to Self-Controlled Video Feedback for Children Learning the Snatch Movement in Weightlifting

Abstract: Our aim in this study was to examine, via technical performance analysis and speed of execution, whether information processing and technical knowledge help explain learning benefits of self-controlled video feedback in children’s weightlifting performance. We randomized 24 children (aged 10 to 12 years) into self-controlled (SC) and yoked (YK) feedback groups. Learners underwent test sessions one week before (pre-test) and one day after (post-test) six weightlifting training sessions. During each test session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Concerning the Dx2, DxL, DxT, VTR, and Diff-Tr parameters, the obtained results showed no change. These results are coherent with those of Souissi et al, 15 who suggested that this result may be explained by the fact that learners who have little prior knowledge are not capable of grasping relevant information from the total amount of information displayed in the video.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Concerning the Dx2, DxL, DxT, VTR, and Diff-Tr parameters, the obtained results showed no change. These results are coherent with those of Souissi et al, 15 who suggested that this result may be explained by the fact that learners who have little prior knowledge are not capable of grasping relevant information from the total amount of information displayed in the video.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the active participation of the learner in the learning process improves performance compared to the traditional one-way knowledge transmission model where content is passively delivered to learners. 13 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 It also favors a further active engagement in the acquisition phases 6,17 and a deeper cognitive commitment during the task. This is translated in terms of higher levels of preparation, 18 performance errors identification capacity, 6,8,19 task recall, 11,20 and feedback processing, 14 which altogether contribute to optimal learning. According to the above arguments, one of the main advantages of self-controlled video feedback group over the other-imposed feedback group lies in the possibilities to intentionally arrange, shape, and optimize relevant information with regard to the cognitive apparatus of learners.…”
Section: Introductionmentioning
confidence: 99%
“…3 A previous study, reported that the combination of video demonstration by an expert and the video feedback, during learning of gymnastics skills, induces more optimized performance than video feedback only. 4 In addition, Aiken et al 5 and Souissi et al 6 argue that the delayed combination between video demonstration and self-controlled video feedback improves the technical performance in complex tasks.…”
Section: Introductionmentioning
confidence: 99%